2014
DOI: 10.1080/13102818.2014.947704
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of cytotoxicity of detonation nanodiamond particles with an osteosarcoma cell line and primary mesenchymal stem cells

Abstract: Recently, nanodiamonds (NDs) have attracted great interest due to their unique physical and chemical properties that could be used in various biological applications. However, depending on the origin, NDs often contain different impurities which may affect cellular functions and viability. Therefore, before their biomedical application, the cytotoxicity of newly produced NDs should be assessed.In the present study, we have evaluated cytotoxicity of four types of ND particles with two cell models: a human osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Also the experiments conducted by Huang et al [13] and Liu et al [18] with the use of different types of cells (macrophages, HT29, A549 and HFL-1 human cells) confirmed that nanodiamonds did not reduce their viability. On the other hand, it is known that nanodiamond toxicity may be material-, cell-and exposure condition-specific [19,23,32,38]. In most of the experiments concerning nanodiamond toxicity it was found that cell treatment with particles up to 24 h did not result in any toxic effect.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Also the experiments conducted by Huang et al [13] and Liu et al [18] with the use of different types of cells (macrophages, HT29, A549 and HFL-1 human cells) confirmed that nanodiamonds did not reduce their viability. On the other hand, it is known that nanodiamond toxicity may be material-, cell-and exposure condition-specific [19,23,32,38]. In most of the experiments concerning nanodiamond toxicity it was found that cell treatment with particles up to 24 h did not result in any toxic effect.…”
Section: Discussionmentioning
confidence: 95%
“…The authors used two types of cells, rat mesenchymal stem cells (rMSCs) and a human osteosarcoma cell line (MG-63) to find which cells were more sensitive to the studied nanoparticles. It was found that they had different sensitivity towards nanodiamond particles e the cytotoxic effect was more evident in rMSCs [23]. Moreover, the results demonstrated the influence of the purification method on cytotoxicity of nanodiamonds.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations